Computing Thermal Bridge of VIP in Building Retrofits using DesignBuilder. (November 2015) - Boafo, Fred Emond; Ahn, Jong-Gwon; Kim, Jun-Tae; Kim, Jin-Hee
Abstract: A high-performance insulation solution, such as vacuum insulation panel (VIP) reduces heat losses in a retrofitted building envelope. However, discontinuity of insulation material causes thermal bridges. A significant thermal bridge effect at the edge of VIP must be taken into account in the overall heat transfer coefficient ( U -value) calculation; but is often omitted due to difficulties especially with numerical calculations. This study describes a modeling approach used to accurately evaluate the effect of thermal bridges on the overall U -value of building envelope. The thermal bridge and U -value were modeled and computed respectively using DesignBuilder which is based on EnergyPlus dynamic simulation engine. Correlation was drawn between experimentally determined U -value of VIP retrofitted building walls and the principal computation parameter.